Evaluasi Pengalaman Pengguna pada Aplikasi Mobile Editing Foto Pixellab Menggunakan User Experience Questionnaire (UEQ) - Rivaldi Setia Zaeni; Fidi Supriadi (Asosiasi Profesi Telekomunikasi dan Informatika Indonesia, 2026)
The rapid development of mobile photo editing applications has increased the need for applications that provide a positive user experience. Pixellab is one of the most widely used mobile photo editing applications due to its comprehensive design and typography features. However, the availability of numerous features does not always guarantee user satisfaction. This study aims to evaluate the user experience of the Pixellab application using the User Experience Questionnaire (UEQ) method. The research employed a quantitative approach involving 69 active Pixellab users in Indonesia. Data were collected through the standard UEQ questionnaire consisting of six dimensions: Attractiveness, Perspicuity, Efficiency, Dependability, Stimulation, and Novelty. The collected data were analyzed using the UEQ Data Analysis Tool to obtain the mean score for each dimension. The results indicate that Pixellab provides a positive user experience, with the highest scores achieved in Efficiency and Dependability dimensions. Nevertheless, the Novelty dimension obtained a relatively lower score compared to other dimensions, indicating the need for interface innovation and feature enhancement. The findings of this study can serve as recommendations for developers in improving the overall user experience of the application.